KETERAMPILAN BERBAHASA SISWA SEKOLAH DASAR DALAM PEMBELAJARAN BAHASA INDONESIA: SYSTEMATIC LITERATURE REVIEW - Nidiana Fauzan; Regina Dwinasti; Suci Amelia; Tri Ananda; Hijrah Afrani; Wisma Rani Sukma; Naila Tuljannah; Azwan Afandy; Putri Hana Pebrina (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Language skills are fundamental competencies that elementary school students must possess as a foundation for academic and social success. Language skills encompass four main aspects: listening, speaking, reading, and writing, which are interrelated and develop gradually according to student characteristics. This study aims to systematically review research results related to elementary school students' language skills published in national journals accredited by Sinta 4-5. The method used is a systematic literature review (SLR) with stages of identification, selection, quality evaluation, and data synthesis. A total of 15 articles published in the last 10 years (2015-2025) were analyzed in depth. The results of the study indicate that the improvement of elementary school students' language skills is influenced by innovative learning strategies, the use of contextual learning media, and the role of teachers in creating a supportive literacy environment. These findings emphasize the importance of integrating communicative and literacy approaches in Indonesian language learning in elementary schools.